Proceedings of the Seventh Annual ACM/IEEE International Conference on Human-Robot Interaction 2012
DOI: 10.1145/2157689.2157702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changing reliability on trust of robot systems

Abstract: Prior work in human-autonomy interaction has focused on plant systems that operate in highly structured environments. In contrast, many human-robot interaction (HRI) tasks are dynamic and unstructured, occurring in the open world. It is our belief that methods developed for the measurement and modeling of trust in traditional automation need alteration in order to be useful for HRI. Therefore, it is important to characterize the factors in HRI that influence trust. This study focused on the influence of changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 19 publications
9
113
2
1
Order By: Relevance
“…A one-way two-tailed Student's t-test revealed that the mean of the pre-session trust assessments across all users and all sessions (including practice sessions) was significantly different from 0.5 (p < 0.05). This positivity bias is consistent with similar findings in other human-robot studies [5,6]. Looking at the average user responses, the gain in trust in reaction to the highperformance boundary tracker settings of Baseline is logically expected, and similarly so are the losses in trust due to failures during the PoorStart and RobotFault scenarios.…”
Section: Session Order Effects and Properties Of Pre-session Trustsupporting
confidence: 89%
See 4 more Smart Citations
“…A one-way two-tailed Student's t-test revealed that the mean of the pre-session trust assessments across all users and all sessions (including practice sessions) was significantly different from 0.5 (p < 0.05). This positivity bias is consistent with similar findings in other human-robot studies [5,6]. Looking at the average user responses, the gain in trust in reaction to the highperformance boundary tracker settings of Baseline is logically expected, and similarly so are the losses in trust due to failures during the PoorStart and RobotFault scenarios.…”
Section: Session Order Effects and Properties Of Pre-session Trustsupporting
confidence: 89%
“…This event-centric view also differentiates our investigations from the majority of studies in the literature, which have characterized impacts on trust from aggregated interaction experiences on longer-term time scales (e.g. [5,8,21]). …”
Section: Event-centric Perspectivementioning
confidence: 69%
See 3 more Smart Citations